Hubungan Tingkat Spiritualitas dan Self-Efficacy Dengan Penerimaan Diri Pada Orang Dengan HIV (ODHIV) Di Puskesmas Poncol Kota Semarang - Dela Arum Lorensa; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Journal of Medical Practice and Research, 2025)
This study aimed to analyze the relationship between spirituality level and self-efficacy with self-acceptance among people living with HIV (PLHIV) at Poncol Primary Health Center, Semarang City. A quantitative cross-sectional design was applied involving 64 PLHIV selected using the Slovin formula. Data were collected using standardized questionnaires measuring spirituality, self-efficacy, and self-acceptance. Statistical analysis was conducted using Spearman’s rho test. The results indicated that most respondents had moderate levels of spirituality, self-efficacy, and self-acceptance. Bivariate analysis revealed a significant and strong positive correlation between spirituality and self-acceptance (r = 0.769; p < 0.001), as well as between self-efficacy and self-acceptance (r = 0.713; p < 0.001). These findings suggest that higher spirituality and stronger self-efficacy are associated with better self-acceptance among PLHIV. Spirituality provides meaning and emotional resilience, while self-efficacy strengthens individuals’ confidence in managing their condition and daily challenges. This study highlights the importance of integrating spiritual and psychological empowerment approaches into comprehensive HIV care services to enhance psychosocial well-being and adaptive capacity among PLHIV.